Laws and sexual prejudices in the Italian positivist culture: murderous mothers and the education to infanticide - Loconsole, Matteo (Studi sulla Formazione/Open Journal of Education, 2019)
The aim of this specific work is to locate the Italian debate about the “infanticide honoris causa” within the positivist culture of the end of 19th century. First of all, the paper will make the reader familiar with the debate concerning the objectivity of human sciences by studying how these sciences faced the issue of female sexuality; it will also describe the patriarchal definition of the relationship between gender and social roles. In order to accomplish this task, the paper will report on the studies of Italian scholars and scientists such as Paolo Mantegazza, Cesare Lombroso, Giuseppe Sergi etc. The paper also tackles the issues of the female sexual sensitivity, dealing with the old prejudice of women’s inferiority together with the cultural perception of motherhood as traditionally intended by the Italian culture. This research study shows how the social relationship between men and women can be seen under different perspectives. Finally, the main purpose of the present paper is to bring to light the different social cultural perception of the infanticide mother as it is well exposed by the gynecologist Muzio Pazzi together with the lawyer Vincenzo Mellusi, two personalities with a deep expertise on the study of this specific crime.